Persepsi masyarakat terhadap kualiti perkhidmatan klinik-klinik kerajaan dan swasta di Lembah Kelang - Raja Jamaluddin,R.A.M.,; Rosman, M.R.,; Azmi, M.T.,; Hanafiah, M.S.,; Rozlan, I.,; Syed Mohamed,A., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1999)
A community survey involving 4,035 respondents was conducted in the Klang Valley in 1997. Result shows that the respondents were satisfied with all aspects of service at both government and private clinics, except for ‘waiting time’ at government clinics. Overall, only 14.5% of respondents were not satisfied with services at government clinics and 2.0% were not satisfied with services at private clinics.However, respondents were more satisfied with all aspects of care at private clinics compared with government clinics (p<0.01). Respondents were willing to pay a median of RM5.00 for services at government clinics compared to RM15.00 for services at private clinics.